Novo gene de resistência ao PepYMV em Capsicum annuum L. - Rezende, Jéssica Figueiredo (2015)
Genetic variability in Capsicum has been exploited to control virus plant diseases caused by potyvirus complex, which can be imparted by at least one of the pvr genes described in literature. Among these described genes, only Pvr4 and Pvr7, both closely linked on Capsicum chromosome 10, have dominant monogenic inheritance. The Pvr4 gene is linked to a codominant marker, for which the resistant allele is associated to the 444 pb band pattern and the susceptible allele is associated to the 458 pb band pattern. The objective of this research was to determine if the resistance found in pepper genotypes, and which are not associated to the CAPS marker Pvr4, is allelic to this gene. Genotypes resistance to PepYMV were evaluated in a greenhouse at HortiAgro Sementes SA, located in Ijaci, Minas Gerais, Brazil. Genotyping was done in the Molecular Genetics Lab, of the Biology Department at the Universidade Federal de Lavras, Lavras, Minas Gerais, Brazil. The genotypes used in this trial were the following: Myr-29-10, carrying Pvr4 gene (P1 with a band pattern of 444 pb); PIM-025 (P2 with a band pattern of 458 pb); F1 (P1 x P2); F2 (P1 x P2); BC1(P1) = {[F1 (P1 x P2)] x P1}; BC1(P2) ={[ F1 (P1 x P2)] x P2}; MagaliR; Konan-R; Mallorca; Criollo de Morelos 'CM-334-UFV'; Criollo de Morelos 'CM-334-INRA'; PIM-HE-133; PIM-013 and Ikeda. From the F2 generation and its segregation, the results indicated that the resistance found in the genotype PIM-025 is not associated with the Pvr4 marker, and the presence of band pattern Pvr4+/Pvr4+ is due a different gene from those described in the literature so far.